Learning Needs Analysis In Elementary School: Differentiated Learning With A Humanistic And Pluralistic Approach - Novianti, Nita; Marini, Arita; Maksum, Arifin; Nurhasanah, Nina; Zakiah, Linda (Universitas Pakuan, 2025)
Diversity is something we often encounter, one of which is in the classroom. However, this is also often a problem if not handled properly. One of the learnings that pays attention to diversity is differentiated learning. Differentiated learning is learning that is adjusted to students' learning needs that are adjusted to their interests, talents, and abilities. One approach that can be integrated with differentiated learning is the humanistic and pluralistic approach. The purpose of this study is to analyze learning needs from the perspective of teachers and students related to differentiated learning that integrates humanistic and pluralistic approaches. This research method uses Research and Development (R D) research in the initial stage, namely Research and information collecting (Borg, WR Gall, 1983). Data collection techniques by filling out surveys and interviews. The subjects were taken randomly, to 41 grade V teachers and 329 grade V students in 14 elementary schools spread across Sukabumi City. The learning needs in differentiated learning with a humanistic and pluralistic approach are that students and teachers agree that the learning in question must fulfill the principles of differentiated learning (9), the humanistic approach (5), and pluralism (6).